Proceedings of the 15th ACM/IEEE-CS Joint Conference on Digital Libraries 2015
DOI: 10.1145/2756406.2756944
|View full text |Cite
|
Sign up to set email alerts
|

Building Complex Research Collections in Digital Libraries

Abstract: Bibliographic metadata standards are a longstanding mechanism for Digital Libraries to manage records and express relationships between them. As digital scholarship, particularly in the humanities, incorporates and manipulates these records in an increasingly direct manner, existing systems are proving insufficient for providing the underlying addressability and relational expressivity required to construct and interact with complex research collections. In this paper we describe motivations for these "workset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
2

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Since item‐level metadata is frequently desirable even for collection‐level research, the HTRC developed a separate triplestore (i.e., a purpose‐built database for semantic data) in which to maintain a Linked Data‐compliant version of the HTDL's MARC records. We considered a number of different off‐the‐shelf ontologies (Nurmikko‐Fuller et al 2015, Jett et al 2016b, Nurmikko‐Fuller et al 2016) before adopting the LoC's BIBFRAME 2.0.…”
Section: Bibframe Metadata Conversionmentioning
confidence: 99%
“…Since item‐level metadata is frequently desirable even for collection‐level research, the HTRC developed a separate triplestore (i.e., a purpose‐built database for semantic data) in which to maintain a Linked Data‐compliant version of the HTDL's MARC records. We considered a number of different off‐the‐shelf ontologies (Nurmikko‐Fuller et al 2015, Jett et al 2016b, Nurmikko‐Fuller et al 2016) before adopting the LoC's BIBFRAME 2.0.…”
Section: Bibframe Metadata Conversionmentioning
confidence: 99%
“…Recent work with the HathiTrust Research Center in the ElEPHãT project has demonstrated the need to construct and interact with complex research collections or worksets. These require extensions to existing bibliographic ontologies in order to represent the items and their relationships comprehensively [17]. Further consideration of DMO as workset is an important line of enquiry which is set to bring insights from digital scholarship back into the music domain.…”
Section: Digital Music Objectsmentioning
confidence: 99%
“…Because digital libraries (DLs) are increasingly adopting Linked Data format standards (e.g., through the application of RDF‐based ontologies) suggests that old interoperability gaps (Haslhofer & Klas, ) between DLs using differing metadata vocabularies can be bridged, opening opportunities for humanities scholars to build research corpora across disparate, independently provided DL platforms. However, while Linked Data resources conform to a singular underlying data model, Nurmikko‐Fuller et al () and Jett et al (2016) demonstrate that large gaps still remain among the competing semantics of similar but non‐equivalent domain models set forth by various ontologies and deployed by different DL and collections platforms.…”
Section: Introductionmentioning
confidence: 99%